1978
DOI: 10.1063/1.324791
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of coercivity in LPE garnet films

Abstract: We have observed that thicker than normal LPE bubble garnet films (14–17 μm) have lower coercivity than those of normal thickness (3–5 μm). We have investigated this thickness dependence of 4 film compositions in the SmCaGe garnet system. In thin films, coercivity is dominated by a high coercivity region near the substrate. As the film thickness increases, the coercivity decreases approaching a ’’bulk’’ value. The two portions of the film, with their different properties, produce a linear relationship of coerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The serious problem was to keep a low coercivity of the films. It was observed that the lattice mismatch, Sm content, melt composition, growth rate, and point defects had an influence on the coercivity [68][69][70][71][72][73][74].…”
Section: Origin Of Coercivitymentioning
confidence: 99%
“…The serious problem was to keep a low coercivity of the films. It was observed that the lattice mismatch, Sm content, melt composition, growth rate, and point defects had an influence on the coercivity [68][69][70][71][72][73][74].…”
Section: Origin Of Coercivitymentioning
confidence: 99%
“…-= --= 6 Sl.n e ' dr dR (2) where R is the bubble radius, 6 is the wall thickness parameter, r is the amplitude of the radial vector stemming from the bubble center. The angle ~ is the azimuthal anqle used in conjunction with r to specify a position within the film plane.…”
Section: Fundamental Analysismentioning
confidence: 99%
“…(2) and (4l the change in wall energy associated with F(0), summed over all of the anisotropic ions is S1.n -, n, dF( 0J I ' 0 d0 1. (2) and (4l the change in wall energy associated with F(0), summed over all of the anisotropic ions is S1.n -, n, dF( 0J I ' 0 d0 1.…”
Section: Fundamental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…͑2͒. The thickness dependence of coercivity was investigated by a number of authors, [7][8][9] and the H c ϳh Ϫ1 dependence was found to be valid. We also experienced a slight increase of the coercivity in the case of the larger ⌬h values ͑0.8-1.4 m͒, but this change was not significant, compared with the original value of H cw , and the effect resulted in a uniform shift of the H cw (T) curve, without any influence on the step-wise exponential character of the curve or on the breaking points in the semilogarithmic plot.…”
Section: Samplementioning
confidence: 99%